143 years since the migration of the cattle egret Bubulcus ibis (Linnaeus, 1758) from Africa to the Andes - Pulido Capurro, Víctor (2020)
The cattle heron is native of the tropical and subtropical areas of Africa and Asia, from where it arrived on the northeast coast of SouthAmerica in 1877 and extended its distribution range to Central America and North America. It has undergone dynamic demographictransformations that have led to the colonization of vast areas, through a process of world expansion that has turned it into a cosmopolitanbird. Various factors such as its large size, long-distance flight capacity, its omnivore condition, its opportunistic nature, its remarkableability to adapt to new environments; as well as deforestation and the establishment of grasslands for cattle on a large scale, havecontributed to the expansion of its distribution range. In the present work a historical review of the colonization of the cattle heron iscarried out since its arrival to America. Here we would see how geographic and environmental factors have contributed to the distributionof its populations in different ecosystems ranging from the marine coasts up to 4,400 meters high in the Andes of South America. Aswell, this work highlights the importance of meteorological and genetical tools that provide information about the routes that the specieshas followed in conquering new areas.